Outcome of pterygium surgery by using conjunctival autograft attachment with fibrin glue: a prospective study - Kaur, Happy; Maqbool, Babar; Kaur, Manpreet (International Journal of Research in Medical Sciences, 2020)
Background: Pterygium is a degenerative condition of sub conjunctival tissues that proliferates as vascularised granulation tissue to invade cornea. Treatment modalities may be medical or surgical. Objectives were to asses results of pterygium surgery in patients with pterygium, in terms of operative time, post-operative symptoms, overall graft success and post-operative complications conducted at government medical college, hospital, Jammu during one year. Methods: Prospective study conducted on 25 patients by using fibrin glue over a period of one year in upgraded department of ophthalmology at GMC Jammu. Results: Mean operating time was 23.20 minutes by using fibrin glue, severity of post-operative symptoms were less. Graft successfully attached in all cases. Conclusions: Present study concluded that use of fibrin glue associated with less operating time and less post-operative discomfort in terms of severity and duration